2015
DOI: 10.3389/fnbeh.2015.00280
|View full text |Cite
|
Sign up to set email alerts
|

Delay discounting without decision-making: medial prefrontal cortex and amygdala activations reflect immediacy processing and correlate with impulsivity and anxious-depressive traits

Abstract: Humans value rewards less when these are delivered in the future as opposed to immediately, a phenomenon referred to as delay discounting. While delay discounting has been studied during the anticipation of rewards and in the context of intertemporal decision-making, little is known about its neural correlates in the outcome phase (during reward delivery) and their relation to personality. Personality traits that have been associated with increased delay discounting include impulsivity and, potentially, anxiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 107 publications
0
8
0
1
Order By: Relevance
“…This finding supports models suggesting that the vmPFC is the key node involved in “hot” decision-making processes and preferentially influenced by physiological modifications, such as those sensed during emotion processing 44 . Facing an emotional and impulsive trial, stimulation of the vmPFC may have modulated activity in the amygdala, a structure known for exhibiting greater activity when immediate rewards are preferred 40,41 and when processing emotions 7981 . Delay discounting in the emotional trials may have therefore relied more heavily on limbic structures such as the amygdala therefore hampering the effect of vmPFC stimulation on average delay discounting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports models suggesting that the vmPFC is the key node involved in “hot” decision-making processes and preferentially influenced by physiological modifications, such as those sensed during emotion processing 44 . Facing an emotional and impulsive trial, stimulation of the vmPFC may have modulated activity in the amygdala, a structure known for exhibiting greater activity when immediate rewards are preferred 40,41 and when processing emotions 7981 . Delay discounting in the emotional trials may have therefore relied more heavily on limbic structures such as the amygdala therefore hampering the effect of vmPFC stimulation on average delay discounting.…”
Section: Discussionmentioning
confidence: 99%
“…Amygdala damage or disconnection between vmPFC and the amygdala impairs performance on delay discounting tasks in rodents 2931 and contributes to deficits on different decision-making tasks in humans 3237 . The amygdala is also sensitive to the magnitude effect - a well-known effect described as greater discounting of low-magnitude compared to high-magnitude rewards 2,38,39 - and shows greater activity when immediate rewards are preferred 40,41 .…”
Section: Introductionmentioning
confidence: 99%
“…While Lempert & Pizzagalli (36) found that decreased DD was associated with anhedonia in healthy individuals, increased DD has been more frequently associated with increased vulnerability to psychopathology (37). The literature on DD in internalizing disorders is mixed, with reports of increased, decreased, or unchanged DD in individuals with high trait anxiety (3840), and social anxiety (41, 42), but increased DD in MDD (43–45). It is possible that inconsistent findings of increased versus decreased DD in internalizing disorders may relate to the presence or absence of significant anhedonia in the included samples, a feature that is not typically assessed or characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy humans, a high level of impulsivity in a delay discounting task (DD) was associated with higher amygdala activation for winning immediate rewards (Ludwig et al, 2015). Moreover, trait impulsivity was positively correlated with the level of activity in response to reward cues in the anterior cingulate cortex (ACC) and amygdala (Kerr et al, 2015).…”
Section: Introductionmentioning
confidence: 99%